Significance of vocal exercises and effective way for soprano / Mimi Nur Nabila Hasnan - Hasnan, Mimi Nur Nabila (2019)
Vocal exercises is importance to voice students, it helps voice students develop and improve their self on singing during exam. This research focuses on soprano students of Faculty of Music in UiTM Shah Alam, to find out which one the most effective vocal exercises and the effective way for soprano students did before singing. This research will be looking on three main objectives, which is to investigate the significance of vocal exercises towards soprano, to find out an effective way for soprano to do vocal exercises, To identify an appropriate vocal exercises for soprano.